Finite-time H∞ control for discrete-time switched singular time-delay systems subject to actuator saturation via static output feedback - Ma, Yuechao; Fu, Lei (International journal of systems science, 2016)
This study employs the multiple Lyapunov-like function method and the average dwell-time concept of switching signal to investigate the finite-time H ∞ static output-feedback (SOF) control problem for a class of discrete-time switched singular time-delay systems subject to actuator saturation. First, sufficient conditions are presented to guarantee the discrete-time switched singular time-delay system regular, causal and finite-time boundedness. Meanwhile, sufficient conditions are presented to ensure the H ∞ disturbance attenuation level, and the design method of H ∞ SOF controller is developed by solving matrix inequalities optimisation problem without any decompositions of system matrices and equivalent transformation. Finally, the effectiveness and merit of the theoretical results are shown through some numerical examples and several vivid illustrations.